MODEL PENDIDIKAN MULTIKULTURAL DI PONDOK PESANTREN - Suheri Suheri; Yeni Tri Nurrahmawati (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
This research presents findings about the model of salaf pesantren education with heterogeneous santri namely; santri devotees, pure santri, student santri and student by exploring models, methods, learning strategies that have the content of multicultural education. Thus multicultural education must be approached holistically and integratively, this research seeks to explore some important parts of pesantren such as tradition, habbitus, ideology and implementation of the values of multiculturalism articulated in the form of curriculum and learning, the vision and life of santri in applying the principles of the principle of complex multicultural education. The pesantren studied has a strong vision and perspective and a unique understanding of multiculturalism, although the understanding still has to develop appropriate and simultaneous strategies and programs for the achievement of objectives. The results of these findings are expected to give contribution in describing the model of cultural education through religious values in the context of the reality of cultural pluralism in boarding school Kauman Alhasani Allathifi Bondowoso and become a reference for education outside of pesantren which still uphold the bulkhead and intellectual egoism and institution.